Surface IgM mediated regulation of RAG gene expression in E mu-N-myc B cell lines. - Ma, A (1992)
Transgenic mice carrying either the c-myc or N-myc oncogene deregulated by the immunoglobulin heavy chain enhancer element (E mu) develop both pre-B and B cell lymphomas (E mu-c-myc and E mu-N-myc lymphomas). We report here that B cell lines derived from these tumors, as well as a line derived from v-myc retroviral transformation, simultaneously express surface immunoglobulin (a hallmark of mature B cells) as well as a common subset of genes normally restricted to the pre-B stage of development-including the recombinase activating genes RAG-1 and RAG-2. Continued RAG-1 and RAG-2 expression in these lines is associated with VDJ recombinase activity detected with a VDJ recombination substrate. Cross-linking of the surface immunoglobulin on these lines with an anti-mu antibody leads to rapid, specific and reversible down-regulation of RAG-1 and RAG-2 gene expression. We also find that a small but significant percentage of normal surface immunoglobulin bearing bone marrow B cells express the RAG-1 gene. These findings are discussed in the context of their possible implications for the control of specific gene expression during the pre-B to B cell transition.